PLASMA PYROLYSIS OF HYDROCARBON GASES - Messerle, V.E.; Ustimenko, A.B. (Recent Contributions to Physics, 2011)
This paper presents the results of numerical and experimental study of hydrocarbon gas plasma pyrolysis. Prospects and abilities of this technology for hydrogen and technical carbon (soot) are considered.